Pengaruh Kualitas Produk, Kualitas Pelayanan dan Persepsi Harga terhadap Keputusan Pembelian di Richeese Factory Majalengka - Latifah, Siti Rubaiatul; Krisna Mutiara Wati (Jurnal Inovasi Bisnis Manajemen dan Akuntansi, 2024)
Fast food companies have gained a lot of popularity in Indonesia in recent years. Fast food restaurants have become a popular choice among the public, because of their convenience and speed in meeting needs. One of them is Richeese Factory which continues to grow and is increasingly popular in various major cities in Indonesia. One of them is in Majalengka district. This study aims to determine the effect of product quality, service quality and price perception on purchasing decisions at Richeese Factory Majalengka. This study is a quantitative study using a non-probability sampling technique with a purposive sampling method. The data collection technique uses a survey technique of 108 respondents. Data analysis in this study uses a testing tool, namely SPSS Software Version 25.0. The results of this study show that there are indicators that greatly influence the variables of product quality, service quality and price perception on purchasing decisions, namely appearance, product innovation, guarantees, physical evidence, and price suitability with product quality. In conclusion, the variables of product quality, service quality and price perception have a simultaneous effect on purchasing decisions at Richeese Factory Majalengka